(untitled) (ACTA MEDICA PERUANA, 2023)
Introduction. Pediatric systemic lupus erythematosus (pSLE) represents 15% of all SLE patients. Renal and neuropsychiatric involvement are more aggressive in pSLE, and single organ involvement is the most commonly found clinical form. Conditions such as cerebral infarction and serositis are unusual manifestation of pSLE. Therapy for pSLE is not different from that for the adult forms, and the therapy armamentarium is the same. Rituximab (RTX) is a worldwide used biological for SLE, with excellent results; however, there is still no consensus with respect to is real efficacy in pSLE. Objectives. Presentation of two pSLE cases with cerebral infarction and serositis as main characteristics, who did not respond to conventional therapy, but who did respond to RTX. Methods. Case report, describing the clinical presentation, diagnostic methods, and therapy approach used. Results. First case: This is a sixteen-year-old girl who was brought because of progressing headache and a tonic-clonic crisis. The brain CT scan showed a left frontoparietal cerebral infarction. Physical examination revealed livedo reticularis in both legs, joint pain, hair loss, and mouth ulcers. Laboratory tests revealed normocytic anemia, thrombocytopenia, reduced complement, 1/320 ANA with a homogeneous pattern, 3.200 mg 24-hour proteinuria, and negative anti-phospholipidic antibodies. A pSLE diagnosis was made, with renal, neurologic, and hematologic involvement, so it was decided to use methylprednisolone, 1 gram IV per day for three days, and then switch to cyclophosphamide 1 g IV per month for 6 months. After three months, proteinuria, fatigue, and arthralgia persisted. For this reason, it was decided to administer rituximab, 375 mg/m2 in days 1 and 15, every six months. After four infusions, proteinuria, joint pain and malaise all disappeared. Nowadays this patient maintains SLEDAI-K scores in remission, and she is also receiving low-dose prednisone. Second case: This is a ten-year-old boy, who presented with abrupt diffuse abdominal pain associated with (abdominal) distention. Other manifestations were tiredness, shortness of breath, and palpitations. A plain abdomen X-ray film did not show hydro-aerial levels, but the chest X-ray film showed bilateral pleural effusion, and enlarged cardiac silhouette. Cardiac ultrasonography and abdominal ultrasonography revealed pericardial effusion and ascites, respectively. Findings in physical examination showed pallor translucid edema of the legs, pericardial throbbing, and reduced respiratory sounds in both pulmonary bases. Laboratory tests revealed leukopenia, lymphopenia, normocytic anemia, elevated acute phase reactants, ANA 1/560, antiDNA 280 U/mL, reduced complement, elevated transaminases, and normal urea and creatinine. pSLE was diagnosed, and therapy instituted was methylprednisolone 30 mg/Kg/dose for 4 days, then it was switched to mycophenolate 600 mg/m2 per day. There was improvement initially, but after two months, serositis reappeared. Then it was decided to start rituximab 375 mg/m2 . After the second infusion, serositis disappeared, and CBC, complement, and transaminase values returned to normal. Nowadays the patient is in remission, and he is receiving low-dose prednisone. Conclusión. Both presented cases featured cerebral infarction and serositis. They also showed high ANA titers and reduced complement. Both patients improved their condition with rituximab after failure with cyclophosphamide and mycophenolate. Informed consent from both parents and patients was obtained.